PH-Dependent solution dynamics of a manganese(ii) polyoxometalate, [Mn4(H2O)2(P2W15O56)2]16−, and [Mn(H2O)6]2+. Issue 44 (22nd October 2015) - Sharma, Rupali; Zhang, Jie; André Ohlin, C.
Abstract : The NMR-determined pH-dependent water–ligand exchange rate of a Mn(ii )-polyoxometalate varies by more than an order of magnitude, in contrast with those of a hexa-aqua ion. Abstract : The aqueous reaction dynamics of the manganese(ii )-functionalised Wells–Dawson polyoxometalate [Mn4 (H2 O)2 (P2 W15 O56 )2 ] 16− has been determined as a function of pH using variable temperature 17 O NMR, and compared with that of the well-studied monomeric manganese(ii ) hexa-aqua ion, [Mn(H2 O)6 ] 2+ . While the rate of aquo–ligand exchange on the hexa-aqua ion remains independent of pH in the range 3.2–6.0, the rate of water exchange of the polyoxometalate ion varies by a factor of fifteen, from 1.98 × 10 7 s −1 at pH 3.2 to 1.3 × 10 6 s −1 at pH 6.0. This decrease in the rate of exchange correlates with the deprotonation of the polyoxometalate framework.